Pengembangan Media Video Animasi 3D Dalam Permainan Tradisional Petak Benteng Untuk Keterampilan Motorik - Dinar Ayu Mirunggan Sari; Murtono; Irfai Fathurohman (Risenologi, 2021)
The purpose of this research is to explain the ddevelopment of 3D animated video media in traditional games of petak benteng for motor skills. The children (students) began to recognize the traditional game of petak benteng. Researchers developed a traditional game of petak benteng by using it as a 3D animated video to introduce the game. So that the game is not inferior to modern games. This researcher is a research and development (RnD). Sources of fata in this study are primary data and secondary data. The data techniques, and interviews. The result of this research is that 3D aniamtion video learning media for students tradisional games, 3D animation video for the introduction of traditional games can be used to improve studentts motor skills, and 3D animation videos can be used as online learning media.